Screening and Optimization of L-Methioninase Production by Gram-Negative Bacteria from Various Hospitals in Baghdad City - Zahraa Mohammed Wahib; Sahira Nsayef Muslim; Farha A. Ali Shafi (Iraqi Journal of Industrial Research)
L-methioninase, a pyridoxal 5′-phosphate dependent enzyme that catalyze degradation of L-methionine to ammonia, methanethiol and α -ketobutyrate. L-methioninase had received a lot of interest for its importance, so to improve the production of L-methioninase, media optimization was done. In this study, clinical isolates of gram-negative bacteria have been collected from several hospitals located in Baghdad city, these isolates were Escherichia coli, Pseudomonas aeruginosa, Klebsiella pneumoniae, Acinetobacter baumannii and Serratia marcescens. The screening for detecting L-methioninase production was performed by semi-quantitative and quantitative analysis, the results revealed that out of all obtained isolates, 31(41.33%) were L-methioninase producers from semi-quantitative screening while by quantitative method only 16 isolates out of these 31 isolates revealed specific activity ranged from 0.19 to 1.15 U/mg and the maximum specific activity was for E. coli U8, which was chosen as best producer isolates. The L-methioninase activity reached its maximum level when E. coli U8 was cultivated with the best conditions, which is consisted of using modified mineral salt M9 broth medium supplemented with L-methionine mixed with galactose (2 g/L) as carbon source and L-glutamine (1.5 g/L) and incubated at 37°C for 48 hours at pH 7.